Solution-Focused Brief Therapy for Major Depressive Disorder: A Single Case Study - Hira Liaqat; Aisha Saleem (NUST Journal of Social Sciences and Humanities, 2022)
Marital problems are one of the leading causes of depression in low income countries. In collectivistic cultures, inability to bear child makes individual more vulnerable towards depression. An increasing body of literature suggests the efficacy of solution-focused brief therapy for depressive disorders. People with eagerness to see change and not showing response for cognitive behaviour therapy respond to solution-focused brief therapy. This case study describes the course of major depressive disorder in a 39-year-old female and treatment strategy of solution-focused brief therapy. The client in this case responded to the therapy and also showed optimistic change in her attitude. Treatment implications of solution-focused brief therapy with its effectiveness on females with major depressive disorder have been discussed in the article.